Metabolic Studies of Vitamin K1-14C and Menadione-14C in the Normal and Hepatectomized Rats - Losito, R; Owen, C. A, Jr.; Flock, E. V; Rochester, Minnesota (Thrombosis and Haemostasis, 1968)
The metabolism of vitamin K1-14C and menadione-14C (vitamin K3-14C) was studied in normal and hepateetomized rats. After the administration of menadione, about 70% of the 14C was excreted in the urine in 24 hrs in both types of rats. Two urinary metabolites were identified by enzymatic hydrolysis: one a glucuronide and the other a sulfate of reduced menadione. Thus, the liver is not necessary for the metabolism of menadione. In the vitamin K1 studies, the intact rats excreted only 10% of the 14C and the hepatectomized rats excreted less than 0.5%. The retention of vitamin K1 may explain its superiority over menadione as an antidote for overdosages of oral anticoagulants.